2014
DOI: 10.1016/j.pmn.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reiki Therapy on Pain and Anxiety in Adults: An In-Depth Literature Review of Randomized Trials with Effect Size Calculations

Abstract: Objective To calculate the effect of Reiki therapy for pain and anxiety in randomized clinical trials. Data Sources A systematic search of PubMed, ProQuest, Cochrane, PsychInfo, CINAHL, Web of Science, Global Health, and Medline databases was conducted using the search terms pain, anxiety, and Reiki. The Center for Reiki Research was also examined for articles. Study Selection Studies that used randomization and a control or usual care group, used Reiki therapy in one arm of the study, published in 2000 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 36 publications
3
57
0
8
Order By: Relevance
“…Our findings correlate with other studies and systematic reviews that demonstrated benefits of Reiki including increased well-being (Catlin & Taylor-Ford, 2011), reduced fatigue and mood disturbance (Post-White et al, 2003) and lowered pain and anxiety (Thrane & Cohen, 2014). Other studies have shown that people having Reiki partly do so to take control and to promote self-management and self-healing (Kelly et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Our findings correlate with other studies and systematic reviews that demonstrated benefits of Reiki including increased well-being (Catlin & Taylor-Ford, 2011), reduced fatigue and mood disturbance (Post-White et al, 2003) and lowered pain and anxiety (Thrane & Cohen, 2014). Other studies have shown that people having Reiki partly do so to take control and to promote self-management and self-healing (Kelly et al, 2004).…”
Section: Discussionsupporting
confidence: 89%
“…Nurses can become attuned and provide Reiki to their patients frequently at no cost (Crawford, Leaver, & Mahoney, 2006;Thrane & Cohen, 2014). Therefore, nurses can use Reiki as part of the application of nonpharmacologic therapeutic interventions for pain management.…”
Section: Discussionmentioning
confidence: 99%
“…While many energy modalities are not well studied, several reviews provide evidence‐based information that can be helpful to patients who are dealing with pain and who may wonder if CAM can augment traditional pain relief treatment. Although little high‐quality research has been done on the effect of Reiki on pain, Thrane and Cohen 34 conducted a literature review with effect‐size calculations and found that Reiki may be effective in reducing pain and anxiety in adults, though larger studies are needed. A Cochrane review of the literature on healing touch, therapeutic touch, and Reiki combined revealed a modest effect in pain relief, though the authors comment that the larger therapeutic effects were attributed to the Reiki studies and that the experience of the practitioner played a role in the effectiveness of the therapy 35 …”
Section: Understanding the Complementary Health Approach To Pain Therapymentioning
confidence: 99%